Operative Wound Complications Following Total Ankle Arthroplasty. (April 2017) - Gross, Christopher E.; Hamid, Kamran S.; Green, Cynthia; Easley, Mark E.; DeOrio, James K.; Nunley, James A.
Background: Wound complications following total ankle replacement (TAR) potentially lead to devastating consequences. The aim of this study was to compare the operative and demographic differences in patients with and without major wound problems which required operative management. We hypothesized that increased tourniquet and operative time would negatively influence wound healing. Methods: We identified a consecutive series of 762 primary TARs performed between December 1999 and April 2014 whose data were prospectively collected. We then identified the subset of patients who required a secondary surgery to treat major wound complications (ie, operative debridement, split-thickness skin grafting, and soft tissue reconstruction). All patients requiring a second surgery had operative wound debridement. We then compared the demographics, operative characteristics, and functional scores to see if any differences existed between patients with and without major wound complications. Clinical outcomes including secondary procedures and implant failure rates were recorded. Results: Twenty-six patients (3.4%) had a total of 49 operative procedures to treat major wound issues. Eighteen patients had flaps and 14 had split-thickness skin grafts. The median time to operatively treating the wound was 1.9 (range: 0.5-12.5) months after the index TAR. The median follow-up time from the wound procedure was 12.7 (range: 1.2-170.8) months. Compared to the control group, patients with major wounds had a significantly longer mean surgery (214.8 vs 189.3 minutes, P = .041) time and trended toward a longer median tourniquet time (151 vs 141 minutes, P = .060). Patients without wound complications were more likely to have posttraumatic arthritis, whereas those with wound complications were more likely to have primary osteoarthritis ( P = .006). The control group trended toward having a higher mean BMI (29.5 vs 27.2, P = .056). There were 6 failures in the major wound complication cohort (23.1%), including 2 below the knee amputations. Conclusion: Ankle wounds that required operative management had high failure rates and some resulted in devastating outcomes. We did not find any increase in major wound complications in those with various risk factors as identified by other studies. Given our data, we recommend limiting operative time. While correcting hindfoot and midfoot alignment is important for improving patient functionality and survivorship of the implant, thought should be given to staging the TAR if multiple pathologies are to be addressed at the time of surgery to limit operative time. Level of Evidence: Level III, retrospective comparative series.